The effect of postoperative complications on survival and recurrence after surgery for breast cancer: A systematic review and meta-analysis. (November 2020) - Savioli, F.; Edwards, J.; McMillan, D.; Stallard, S.; Doughty, J.; Romics, L.
Abstract: Background: This systematic review investigated the impact of complications on long term outcomes for patients with primary invasive operable breast cancer. Methods: A systematic review was performed using appropriate keywords, and meta-analysis using a random effects model completed. Results: Ten retrospective cohort studies, including 37, 657 patients were included. Five studies identified a relationship between wound complications, infection and pyrexia and recurrence or recurrence-free survival. Risk of recurrence, 1-year and 5-year recurrence-free survival and overall survival were related to complications, particularly for patients with poor Nottingham Prognostic Index. Five studies failed to demonstrate a relationship between complications and prognosis. Complication was found to significantly affect 5-year recurrence-free survival (HR 1.48 95 % CI 1.02–2.14, p = 0.04) but not recurrence (HR 2.39, 95 %CI 0.94–6.07, p = 0.07), with a high degree of heterogeneity amongst analysed studies (I2 = 95 %). Discussion: Further research is needed to quantify the effects of postoperative complication on prognosis following surgery for breast cancer.